The current economic and financial crisis: a gender perspective - Rania Antonopoulos (Levy Economics Institute of Bard College, 2009)
Widespread economic recessions and protracted financial crises have been documented as setting back gender equality and other development goals in the past. In the midst of the current global crisisoften referred to as the Great Recessionthere is grave concern that progress made in poverty reduction and women's equality will be reversed. Indeed, for many developing countries it is particularly worrisome that, through no fault of their own, the global economic downturn has exacerbated effects from other crises manifest in food insecurity, poverty, and increasing inequality. This paper explores both well-known and less discussed paths of transmission through which crises affect women's world of work and overall wellbeing. As demand for textile and agricultural exports decline, along with tourism, job losses are expected to rise in these femaleintensive industries. In addition, the gendered nature of the world of work suggests that women will see an increase in their share among informal and vulnerable workers worldwide, and will also supply more of their labor under unpaid conditions. The latter is particularly important in the context of developing countries, where many production activities take place outside the strict boundaries of the market. The paper also makes this point: examined through the prism of gender equality, the ability of the state to implement countercyclical policies matters greatly. If policy responses at the national and international levels end up aggravating inequities, gender equality processes face many more barriers, especially among the poor.
Keywords: B5; E24; E61; E62; E64; G10; H1; J16; J21; J38; J48; O23; O24; 330; Economic crisis; gender; employer of last resort; unemployment; poverty; policy objectives; development; fiscal and monetary policy in development; agricultural policies; female employment in textiles and crisis; agriculture and food security